The relationship between depression and self-compassion with non-suicidal self-injury among university students - Idris, Siti Nurfathin; Mahfar, Mastura (International Journal of Public Health Science (IJPHS), 2024)
The non-suicidal self-injury (NSSI) has been reported among university students which must be taken into consideration because it can have a negative impact on students’ well-being and lives. Therefore, this study was conducted to investigate the relationship between depression and self-compassion with NSSI among university students. This study was to identify the levels of depression, self-compassion, and NSSI. Purposive sampling was used in this correlational study and quantitative research design. This study included 73 NSSI reported year 1 and 2 undergraduate students from one of the programs at a Malaysian university. The instruments used in this study were the depression anxiety stress scale-21 (DASS-21) depression subscales, selfcompassion scale (SCS), and inventory of statements about self-injury (ISAS). Findings show that respondents had a moderate level of depression and self-compassion, as well as a low level of NSSI. Findings also demonstrate that there was a significant positive relationship between depression and NSSI. Self-compassion and NSSI had a significant negative relationship. There were also different findings for the relationship between the dimensions of self-compassion and NSSI. In conclusion, NSSI is a risky behavior that has negative consequences among university students.